The rules of survival - Werlin, Nancy (New York : Speak, 2008)
Seventeen-year-old Matthew recounts his attempts, starting at a young age, to free himself and his sisters from the grip of their emotionally and physically abusive mother.
"Bonus material inside"--Cover.
Bonus material: Rules of survival discussion guide.
Accelerated Reader AR
Keywords: Child abuse -- Fiction; Brothers and sisters -- Fiction; Emotional problems of children -- Fiction; Emotional problems -- Fiction; Mentally ill children -- Fiction